Giant osteoclasts in patients under bisphosphonates - Mac-Way, Fabrice (BioMed Central, 2014)
BACKGROUND: Bisphosphonates have been widely used for treatment of high bone resorption states. It lowers bone turnover by inhibiting osteoclasts bone resorption with various mechanisms of actions: inhibition of osteoclast formation and attachment to the bone surface, induction of metabolic injury, alteration of vesicle trafficking and induction of osteoclast apoptosis. Bone biopsies studies from patients under bisphosphonates have shown that some resorption parameters are decreased as expected but the number of osteoclasts seems not to be necessarily decreased. The description of osteoclasts morphology from patients treated with bisphosphonates has rarely been reported in the literature. CASE PRESENTATION: We describe in this paper two patients treated with bisphosphonates from whom iliac crest bone biopsies have shown large, multinucleated and apoptotic osteoclasts that were not associated with bone resorption activities. The characteristics of these osteoclasts are described and the literature reviewed. CONCLUSION: The appropriate recognition of these giant osteoclasts in bone tissues from patients treated with bisphosphonates is of primary importance for bone pathologists and should not be interpreted as signs of increased bone resorption as seen in hyperparathyroidism, bone cancer or Paget’s disease of bone.